A methodology for setting the injection moulding process parameters for polymer rapid tooling inserts. Issue 9 (15th January 2019) - Bagalkot, Anurag; Pons, Dirk; Clucas, Don; Symons, Digby
Abstract : Purpose: Polymer rapid tooling (PRT) inserts can be used as injection moulding (IM) cavities for prototyping and low volume production but lack the robustness of metal inserts. Metal inserts can withstand high injection pressure and temperature required, whereas PRT inserts may fail under similar parameters. The current method of parameter setting starts with using the highest pressure setting on the machine and then fine-tuning to optimize the process parameters. This method needs modification, as high injection pressures and temperatures can damage the PRT inserts. There is a need for a methodical process to determine the upper limits of moulding parameters that can be used without damaging the PRT inserts. Design/methodology/approach: A case study analysis was performed to investigate the causes of failure in a PRT insert. From this, a candidate set-up process was developed to avoid start-up failure and possibly prolong tool life. This was then tested on a second mould, which successfully avoided start-up failure and moulded 54 parts before becoming unusable due to safety issues. Findings: Process parameters that are critical for tool life are identified as mould temperature, injection pressure, injection speed, hold pressure and cooling time. Originality/value: This paper presents a novel method for setting IM process parameters for PRT inserts. This has the potential to prevent failure at start up when using PRT inserts and possibly extend the operating life of the PRT inserts.